The Structure of Unemployment in Poland and the European Union Between 2000 and 2012 - Kwiatkowska, Walentyna (Comparative Economic Research. Central and Eastern Europe, 2014)
This paper has two main objectives. The first is to show changes in the levels of unemployment and unemployment rates in Poland and other European Union countries and to explain why the Polish rates are relatively high. The second is to analyse the structure of unemployment by gender, age, levels of education, and duration of unemployment. In order to assess the Polish unemployment structure it is compared with the analogous structures in the other European Union countries. The analysis will indicate the groups of the labour force with high risk of unemployment. Among the groups of high risk of unemployment are women, youth, people with low skills, and the long-term unemployed.